ACE2 Deficiency Enhances Angiotensin II-Mediated Aortic Profilin-1 Expression, Inflammation and Peroxynitrite Production - Jin, Hai-Yan; Song, Bei; Oudit, Gavin Y.; Davidge, Sandra T.; Yu, Hui-Min; Jiang, Yan-Yan; Gao, Ping-Jin; Zhu, Ding-Liang; Ning, Guang; Kassiri, Zamaneh; Penninger, Josef M.; Zhong, Jiu-Chang (PLOS ONE, 2012)
Inflammation and oxidative stress play a crucial role in angiotensin (Ang) II-mediated vascular injury. Angiotensin-converting enzyme 2 (ACE2) has recently been identified as a specific Ang II-degrading enzyme but its role in vascular biology remains elusive. We hypothesized that loss of ACE2 would facilitate Ang II-mediated vascular inflammation and peroxynitrite production. 10-week wildtype (WT, Ace2+/y) and ACE2 knockout (ACE2KO, Ace2−/y) mice received with mini-osmotic pumps with Ang II (1.5 mg.kg−1.d−1) or saline for 2 weeks. Aortic ACE2 protein was obviously reduced in WT mice in response to Ang II related to increases in profilin-1 protein and plasma levels of Ang II and Ang-(1–7). Loss of ACE2 resulted in greater increases in Ang II-induced mRNA expressions of inflammatory cytokines monocyte chemoattractant protein-1 (MCP-1), interleukin (IL)-1β, and IL-6 without affecting tumor necrosis factor-α in aortas of ACE2KO mice. Furthermore, ACE2 deficiency led to greater increases in Ang II-mediated profilin-1 expression, NADPH oxidase activity, and superoxide and peroxynitrite production in the aortas of ACE2KO mice associated with enhanced phosphorylated levels of Akt, p70S6 kinase, extracellular signal-regulated kinases (ERK1/2) and endothelial nitric oxide synthase (eNOS). Interestingly, daily treatment with AT1 receptor blocker irbesartan (50 mg/kg) significantly prevented Ang II-mediated aortic profilin-1 expression, inflammation, and peroxynitrite production in WT mice with enhanced ACE2 levels and the suppression of the Akt-ERK-eNOS signaling pathways. Our findings reveal that ACE2 deficiency worsens Ang II-mediated aortic inflammation and peroxynitrite production associated with the augmentation of profilin-1 expression and the activation of the Akt-ERK-eNOS signaling, suggesting potential therapeutic approaches by enhancing ACE2 action for patients with vascular diseases.